Recognition of a Nocardia transvalensis complex by resistance to aminoglycosides, including amikacin, and PCR-restriction fragment length polymorphism analysis. - Wilson, R W (1997)
Amikacin resistance, rare among nocardiae, was observed in 58 clinical isolates of nocardiae. All of these isolates hydrolyzed hypoxanthine, and 75 to 100% utilized citrate, D-galactose, and D-trehalose as sole carbon sources. Based on utilization of I-erythritol, D-glucitol, i-myo-inositol, D-mannitol, and ribitol and susceptibility to amoxicillin-clavulanic acid, the 58 isolates were separable into four groups. One group was negative for I-erythritol and ribitol and included all the isolates belonging to Nocardia asteroides complex antibiogram type IV. The remaining three groups were positive for I-erythritol and ribitol and were grouped within Nocardia transvalensis. The group that included the type strain was designated N. transvalensis sensu stricto, and the other two groups were designated new taxons 1 and 2. PCR-restriction fragment length polymorphism (RFLP) analysis of a 439-bp segment of the 65-kDa heat shock protein gene with XhoI and HinfI produced identical patterns for 53 (91%) and 58 (100%) isolates, respectively, and differentiated them from all other Nocardia taxa. NarI- and HaeIII-derived RFLP patterns clearly differentiated each of the four biochemically defined taxa. These four groups were also distinguishable by using the chromogenic substrates in Dade MicroScan test panels. By high-performance liquid chromatography, these isolates exhibited the same unique mycolic acid-ester elution patterns that differed from those of all other clinically significant nocardiae. Gas-liquid chromatographic analysis of fatty acids also produced similar patterns for all isolates that distinguished them from all other Nocardia taxa, but did not differentiate the four taxa within the complex. We propose the designation N. transvalensis complex for these four groups of nocardiae, pending further genetic evaluation.